Digital Public Relations dan Loyalitas Komunitas: Strategi Engagement Perusahaan Logtech di Era Media Sosial - Rachel Jessica; Christian Wiradendi Wolor (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study analyzes the Digital Public Relations strategies of Logtech Company X in building community engagement on Instagram. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observation, and documentation involving three participants: one PR staff member and two active Instagram followers. The data were analyzed to identify communication patterns, engagement strategies, and challenges encountered in the implementation of Digital PR activities. The results revealed three main findings: (1) content management strategies were implemented through four consistent yet flexible brand character pillars, supported by storytelling approaches and modern minimalist visuals; (2) interactive communication was executed through humanizing the brand strategies and standardized two-way response procedures that redirect public discussions to private channels; (3) key communication barriers included generational gaps and the complexity of high-level technology content. These findings indicate that the effectiveness of Digital PR in a B2B context depends not only on content quality but also on the consistency of dialogic interactions and the capacity to humanize the brand in digital spaces. Furthermore, the findings highlight the importance of adaptive communication practices in maintaining audience engagement and strengthening relationships with stakeholders. This research contributes to filling the literature gap regarding digital communication strategies in Indonesia's B2B logistics technology industry.